DINAMIKA POLITIK PERSETUJUAN BERSAMA TENTANG PENETAPAN DESA ADAT DI KABUPATEN ROKAN HULU TAHUN 2014 - Suganda, Haryo; Amin, Raja Muhammad (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This study is motivated the identification of policies issued by the regional Governmentof Rokan Hulu in the form of Regulatory region number 1 by 2015 on the determination of thevillage and Indigenous Village. Political dynamics based on various interests against themanufacture of, and decision-making in the process of formation of the corresponding localregulations determination of Indigenous Villages in the Rokan Hulu is impacted to a verysignificantamount of changes from the initial draft of the number i.e. 21 (twenty one) the villagebecame Customary 89 (eighty-nine) the Indigenous Villages who have passed. Type of thisresearch is a qualitative descriptive data analysis techniques. The research aims to describe theState of the real situation in a systematic and accurate fact analysis unit or related research, aswell as observations of the field based on the data (information). Method of data collectionwas done with interviews, documentation, and observations through fieldwork (field research).The results of the research on the process of discussion of the draft local regulations andmutual agreement about Designation of Indigenous Villages in the Rokan Hulu is, showed thatthe political dynamics that occur due to the presence of various political interests, rejectionorally by Villagers who were judged to have met the requirements of Draft Regulations to beformulated and the area for the set to be Indigenous Villages, and also there is a desire fromsome villages in the yet to Draft local regulations in order to set the Indigenous village , there isa wide range of interests of these aspects influenced the agreement to assign the entire localVillage which is in the Rokan Hulu become Indigenous village, and the village of Transmigrationinto administrative Villages where the initiator of the changes in the number of IndigenousVillages in the Rokan Hulu it is the desire of the local Government of its own.